Computed Cardiographie Pattern Diagnosis - Cady, Lee D., Jr; Simônson, Ehnst; Blackburn, Henby; Taylor, Henry L. (Methods of Information in Medicine, 1965)
Problems encountered in computing electrocardiographic diagnoses will be discussed. The method was to select voltage and time measurements for quantified diagnostic criteria. The selection was based on the physiologic events of the heart, the pathologic involvement for different diseases, the geometry of the lead system and the dispersion and overlap of the diagnostic groupings. It was possible to compute envelope surfaces which enclose each diagnostic grouping of persons. Specific measurements of voltages and times gave a great separation of persons with different diagnoses and little separation of persons with the same diagnoses.